CLASSIFICATION OF METHODS OF THE SIGNAL SEMANTIC WAVELET TRANSFORM FOR IMAGE CONTOUR SEGMENTATION - Polyakova, Marina; Krylov, Victor (International Journal of Computing, 2014)
In this paper the methods of signal semantic wavelet transform which underlines the edges of image in the edge detector task are analyzed and classified.